Pastoral culture and range management: Recent lessons from Maasailand - Grandin, B.E. (1987)
Reviews the appropriateness of three major assumptions underlying pastoral development in East Africa, viz, economic irrationality of pastoralists, the unchanged nature of pastoral production systems, and the applicability of western models to pastoral development.